1974
DOI: 10.1051/rphysap:019740090106900
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting tunnel junction bolometers

Abstract: Two newSome improvement in these values is anticipated.-2-LBL-2222

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 3 publications
(1 reference statement)
1
8
0
Order By: Relevance
“…The resulting NEP=1.7x1o-15 WHz-1/2 with a response time t=83 ms, is comparable to, but not better than, composite bolometers with semiconducting thermometers operated at the same temperature [52] and much less sensitive than semiconducting bolometers operated at lower temperatures. Similar performance was obtained with bolometers which used SNS and SIN tunnel junction thermomgters at 1.5 K and SQUID readouts [53]. None of these bolometers are used because they have similqr performance to the semiconductor bolometers, but the electronic systems are more complicated.…”
Section: Superconducting Bolometersupporting
confidence: 52%
“…The resulting NEP=1.7x1o-15 WHz-1/2 with a response time t=83 ms, is comparable to, but not better than, composite bolometers with semiconducting thermometers operated at the same temperature [52] and much less sensitive than semiconducting bolometers operated at lower temperatures. Similar performance was obtained with bolometers which used SNS and SIN tunnel junction thermomgters at 1.5 K and SQUID readouts [53]. None of these bolometers are used because they have similqr performance to the semiconductor bolometers, but the electronic systems are more complicated.…”
Section: Superconducting Bolometersupporting
confidence: 52%
“…The SNS bolometer is based on the temperature dependence of the critical current in a superconductor-normal metal-superconductor (SNS) junction (Clarke, et al , 1974 Typical structure for a composite bolometer (after Clarke, et al, 1978 Experimental results so far support this conclusion.…”
Section: Fundamental Principles Governing Digital Logic Devicesmentioning
confidence: 99%
“…A bolometer is a rectification device that converts an electromagnetic wave into resistance or voltage change through heat generation; 1 such a device may be used to detect weak electromagnetic waves in radio astronomy and thermography 2 . Various types of bolometers such as semiconductor 3 5 , superconductor 6 8 , and carbon bolometers 9 , 10 have been developed for detecting infrared and millimeter wavelength radiation. Cooled bolometers using a graphene system have been developed over the last two decades and exhibit high responsivity: 11 , 12 Fatimy et al have reported a very high responsivity of 5 × 10 10 V/W at 2.5 K 11 .…”
Section: Introductionmentioning
confidence: 99%